Making a "net" for the net - Nola Campbell; Russell Yates; Clive McGee (Flexible Learning Association of New Zealand, 2012)
The rapid development of open learning has seen a major change in the traditional tertiary student profile. Many new students have come to tertiary education with varying backgrounds that are often limited to less than three years of secondary schooling There has been a major change in the age and background profile of the New Zealand tertiary student population. Open learning has been an influential part of this change by offering the chance for tertiary study to students who not always have gained access in the past. Students whose secondary schooling was limited need strong support if they are to bridge into university study. A programme of teacher education called the Mixed Media Programme (MMP) at the University of Waikato has been delivered successfully for three years. The need to provide strong student support has been an integral part of a programme. It has contributed to a high success rate. This paper discusses the way in which support structures have been devised and implemented. It refers to the support provided by the University as an institution, support from tutors and the way in which students have been encouraged to support themselves.